On the Electropolishing Mechanism of Nickel Titanium in Methanolic Sulfuric acid − An Electrochemical Impedance Study. Issue 15 (24th July 2018) - Fushimi, Koji; Neelakantan, Lakshman; Eggeler, Gunther; Hassel, Achim Walter
Abstract : Electropolishing of NiTi shape memory alloys is possible in methanolic 3 m H2 SO4 . The electro‐dissolution behavior of NiTi in methanolic 3 m H2 SO4 is ascertained in terms of Nyquist plots using electrochemical impedance spectroscopy (EIS) under limiting current flow (mass transfer control) condition. The electro‐dissolution behavior is studied under convective conditions using a rotating disc electrode. The influence of changes in rotation rate, applied potential, and temperature are determined. This study demonstrates that electro‐dissolution under mass transfer condition follows a compact salt‐film mechanism. In order to quantitatively characterize the salt film formed during electropolishing, EIS is performed under stationary conditions. The increase in applied voltage causes an increase in polarization resistance and decrease in capacitance of the interface film. Abstract : This study demonstrates that electro‐dissolution under mass transfer condition follows a compact salt‐film mechanism. In order to quantitatively characterize the salt film formed during electropolishing, EIS is performed under stationary conditions. The increase in applied voltage caused an increase in polarization resistance and decrease in capacitance of the interface film.